2022
DOI: 10.1002/ctd2.139
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome and neurosurgery: Implications for treatment

Abstract: Introduction: The aim of this review is to summarize the current understanding of the gut-brain axis (GBA), its impact on neurosurgery, and its implications for future treatment. Background: An abundance of research has established the existence of a collection of pathways between the gut microbiome and the central nervous system (CNS), commonly known as the GBA. Complicating this relationship, the gut microbiome bacterial diversity appears to change with age, antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 303 publications
(592 reference statements)
0
1
0
Order By: Relevance
“…Therefore, focusing on the VN might help restore the homeostasis of the microbiota-gut-brain axis to treat these diseases. Compelling evidence have shown that VNS can ameliorate gut dysbiosis-induced pro-inflammatory effects, and VNS may rescue decreased gut mucosal integrity by upregulating enteric glial cells, reducing systemic proinflammatory cytokines, promoting recovery as well as modulating immune functions 118 , 119 . With regard to the effect of VNS/ta-VNS on the GM profile, there is only the paper by Haney et al and although their results were neutral, the authors concluded that VNS remains a promising experimental and therapeutic modality for manipulating GM communities 120 .…”
Section: Potential Pathways and Action Mechanisms By Which Ta-vns Has...mentioning
confidence: 99%
“…Therefore, focusing on the VN might help restore the homeostasis of the microbiota-gut-brain axis to treat these diseases. Compelling evidence have shown that VNS can ameliorate gut dysbiosis-induced pro-inflammatory effects, and VNS may rescue decreased gut mucosal integrity by upregulating enteric glial cells, reducing systemic proinflammatory cytokines, promoting recovery as well as modulating immune functions 118 , 119 . With regard to the effect of VNS/ta-VNS on the GM profile, there is only the paper by Haney et al and although their results were neutral, the authors concluded that VNS remains a promising experimental and therapeutic modality for manipulating GM communities 120 .…”
Section: Potential Pathways and Action Mechanisms By Which Ta-vns Has...mentioning
confidence: 99%
“…explores the connection between secondary spinal cord injury (SCI) and gut dysbiosis, disrupting the SCI healing process. [ 5 ] Gut dysbiosis has been shown to prolong locomotive recovery and increase inflammation, which can reduce the potential for functional recovery as well as possibly curtail the development of molecules such as brain-derived neurotrophic factor that are pivotal for neuroplasticity. [ 6 7 ]…”
mentioning
confidence: 99%
“…The secondary effects of TBI after initial stabilization of the patient are disruption of the blood–brain barrier, elevated inflammation within the brain, increased production of reactive oxygen species as well as a dysregulated microbiome because of secondary neurodegeneration seen in TBI. [ 5 8 ]…”
mentioning
confidence: 99%